Insuring new climate risks that affect health - Françoise Gilles; Julia d’Astorg (Field Actions Science Reports)
This joint interview highlights the growing challenges insurers face in understanding and covering all the risks associated with climate change and their impact on health. The many risks that have appeared recently are interconnected and combine with existing threats, making them particularly complex to manage. It is in this context that AXA is striving to find innovative solutions to offer protection to as many people as possible, thereby increasing society's overall resilience.Understanding and managing risk is in the DNA of an insurer. AXA is committed to deciphering emerging risks and new impacts on humankind, drawing on its internal resources and supporting science at a very early stage in laboratories so that it can make sense of the complexity of the world around us. For 16 years, the AXA Research Fund has been accelerating the exploratory capacity of science by supporting researchers through grants. By promoting open, cross-disciplinary and independent science, it enables exploration in new areas of risk science relating to health, the climate, and the economy. This support for the academic world is part of a broader approach – a major focus for AXA – involving alliances between private and public players to tackle the major challenges facing society, particularly climate change and its impact on human health. In this context, insurers play an increasingly crucial role in the economy and the protection of individuals and the environment, driving resilience and innovation for a more sustainable future.